(untitled) (Web of Teachers: Inderscience Research, 2025)
This article discusses the role of modern teaching methods in the educational process, their advantages, and the mechanisms of their application. Unlike traditional teaching, modern methods aim to develop students’ thinking, research, and creativity potential. The article analyzes advanced methods such as interactive methods, problem-based learning, project approaches, ICT-based education, and the flipped classroom. Additionally, it examines modern approaches being implemented in Uzbekistan’s education system, foreign experiences, and existing problems. The article provides practical assistance for teachers, enhances teaching effectiveness, and enables students to become active participants in the learning process.